Development of iPSC-derived T cells targeting EGFR neoantigens in non-small cell lung cancer - Kouta Niizuma; Toshinobu Nishimura; Jonathan Villanueva; Laura Amaya; Jonas L. Fowler; Taichi Isobe; Yusuke Nakauchi; Brandon Saavedra; Haojun Xu; Mahito Nakanishi; Adam C. Wilkinson; Kyle M. Loh; et al. (Molecular Therapy: Methods & Clinical Development)
A long-sought goal of cancer immunotherapy is to mass-produce T cells that specifically target tumor neoantigens. One decisive challenge is the identification of neoantigens derived from cancer driver genes. Here, we identify T cells that recognize the NSCLC-associated EGFR C797S mutation, which confers resistance to current inhibitors and is linked to poor prognosis. To overcome limitations in T cell availability, we reprogrammed EGFR C797S-specific T cells into induced pluripotent stem cells (iPSCs) and re-differentiated them into CD8+ T cells. These iPSC-derived T cells specifically recognized the EGFR C797S mutation and effectively killed cancer cells expressing this mutation. Our findings underscore the potential of targeting driver mutation-derived neoantigens for immunotherapy and demonstrate that iPSC-derived T cells can mediate antitumor effects. Collectively, this approach combining neoantigen identification with T cell reprogramming may offer a promising strategy for targeting drug-resistant tumors.